Performance of Xpert MTB/RIF and sputum microscopy compared to sputum culture for diagnosis of tuberculosis in seven hospitals in Indonesia - Karuniawati, Anis; Burhan, Erlina; Koendhori, Eko Budi; Sari, Desvita; Haryanto, Budi; Nuryastuti, Titik; Gayatri, A. A. A. Yuli; Bahrun, Uleng; Kusumawati, R. Lia; Sugiyono, Retna Indah; Susanto, Nugroho Harry; Diana, Aly; et al. (Frontiers in Medicine, 2023)
Tuberculosis (TB) is a major public health concern in Indonesia, where the incidence was 301 cases per 100.000 inhabitants in 2020 and the prevalence of multi-drug resistant (MDR) TB is increasing. Diagnostic testing approaches vary across Indonesia due to resource limitations. Acid-fast bacilli (AFB) smear is widely used, though Xpert MTB/RIF has been the preferred assay for detecting TB and rifampicin resistance since 2012 due to higher sensitivity and ability to rapidly identify rifampicin resistance. However, < 1,000 Xpert instruments were available in Indonesia as of 2020 and the Xpert supply chain has suffered interruptions. We compared the performance of Xpert MTB/RIF and AFB smear to facilitate optimization of TB case identification. We analyzed baseline data from a cohort study of adults with pulmonary TB conducted at seven hospitals across Indonesia. We evaluated sensitivity and specificity of AFB smear and Xpert MTB/RIF using Mycobacterium tuberculosis (Mtb) culture as the gold standard, factors associated with assay results, and consistency of Xpert MTB/RIF with drug susceptibility test (DST) in detecting rifampicin resistance. Sensitivity of AFB smear was significantly lower than Xpert MTB/RIF (86.2% vs 97.4%, p-value<0.001), but specificity was significantly better (86.7% vs 73.3%, p-value<0.001). Performance varied by hospital. Positivity rate for AFB smear and Mtb culture was higher in subjects with pulmonary cavities. Consistency of Xpert MTB/RIF with DST was lower in those with rifampicin-sensitive TB. Additional evaluation using sputa from primary and secondary Indonesian health centers will increase generalizability of assessment of AFB smear and Xpert MTB/RIF performance and better inform health policy.